2021
DOI: 10.3390/w13192697
|View full text |Cite
|
Sign up to set email alerts
|

Filtering Effect of Rhinogobio cylindricus Gut Microbiota Relieved Influence of the Three Gorges Dam on the Gut Microbiota Composition

Abstract: Fish gut microbiota were potentially influenced by habitat changes. However, the fish gut has been shown to have a filtering effect on habitat microorganisms. Here, we hypothesized that the filtering of fish gut microbiota could counteract the effect of dam construction on the gut microbiota composition. To test this hypothesis, we collected water and Rhinogobio cylindricus individuals from four sampling sites located upstream of the Three Gorges Dam (TGD) and analyzed the microbiota composition in the water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…A subset of approximately 50 g of each sediment sample was separated and frozen at −80 °C for further DNA extraction. Water samples (approximately 500 mL) were filtered using glass fiber (GF/C) with a 0.22 µm aperture for extracting microbial genomic DNA ( Chen et al, 2021 ). The remaining sediment and water samples were used for physicochemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A subset of approximately 50 g of each sediment sample was separated and frozen at −80 °C for further DNA extraction. Water samples (approximately 500 mL) were filtered using glass fiber (GF/C) with a 0.22 µm aperture for extracting microbial genomic DNA ( Chen et al, 2021 ). The remaining sediment and water samples were used for physicochemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The species and number of anaerobic bacteria in the intestine of carnivorous sh were signi cantly higher than those of herbivorous sh (Wang et al, 2018). In Atlantic salmon, soybean meal signi cantly reduced the intestinal microbial diversity, while another study found that the abundance of cyanobacteria and Lactobacillus species in the hindgut of gilthead seabream Sparus aurata gradually increased with an increasing proportion of soybean meal in the feed (Parma et al, 2016;Reveco et al, 2014) In addition, studies have con rmed that the construction of a hydropower station can change the environmental factors of river ecosystems and destroy the original habitats of sh, by altering the water temperature, aquatic microorganisms, dissolved oxygen strati cation, and sh spawning grounds (Ma et al, 2008;Sá-Oliveira et al, 2015;Chen et al, 2021). For example, Chen et al, (Chen et al, 2020) observed that dam construction altered the microbial composition in upstream water and signi cantly increased the relative abundance of harmful Cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al, (Xu et al, 2019) found that construction of the Yin-pan hydropower station severely damaged the spawning sites of upstream sh and signi cantly reduced the annual sh spawning output in the Wujiang River. Datengxia Gorge hydro dam, located on the Qianjiang River, Guangxi, China, controls 56.4% of the Xijiang River basin area, and is a key water conservancy hub in the Pearl River basin and part of the Three Gorges Project (Jiang and Zhu, 2014;Yang et al, 2021). The impacts of hydropower stations on the hydrodynamics and chemical characteristics of rivers and their sh diversity have been widely reported (Fan, 2017; Monaghan et al, 2020;Zhang et al, 2020) Moreover, previous studies have demonstrated that habitat changes potentially in uence the composition of sh gut microbiota (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions of dams have been widely studied in the literature. On the one hand, dams provide great opportunities to meet the needs of human well-being [2], such as flood control, power generation, waterway dredging, and agricultural irrigation [3,4], and it even contributes to social sustainability by generating electricity instead of incinerating the solid fuel [5]. Indeed, dams have been proven to benefit the environment by reducing CO 2 emissions via providing hydropower in China [6].…”
Section: Introductionmentioning
confidence: 99%